Recurrent CSPs after Transcranial Magnetic Stimulation of Motor Cortex in Restless Legs Syndrome - Aulikki Ahlgrén-Rimpiläinen; Hannu Lauerma; Seppo Kähkönen; Juha Markkula; Ilpo Rimpiläinen (Neurology Research International)
Aims. The aim of this study was to investigate the motor control and central silent period (CSP) in restless legs syndrome (RLS). Methods. Transcranial magnetic stimulation was focused on the dominant and nondominant hemispheric areas of motor cortex in six subjects with RLS and six controls. The responses were recorded on the contralateral abductor digiti minimi (ADM) and tibialis anterior (TA) muscles with intramuscular needle electrodes. Results. No significant differences were found in the motor conduction or central motor conduction time, in the latency, or in the duration of the CSPs between or within the groups, but multiple CSPs were observed in both groups. The number of the CSPs was significantly higher in both ADMs and in the dominant TA (P≤0.01) in the RLS group compared to the controls. Conclusion. Descending motor pathways functioned correctly in both groups. The occurrence of the recurrent CSPs predominantly in the RLS group could be a sign of a change of function in the inhibitory control system. Further research is needed to clarify the role of the intramuscular recording technique and especially the role of the subcortical generators in the feedback regulation of the central nervous system in RLS.